A new species of the genus Tonsilla (Araneae: Amaurobiidae) from mountains of Sichuan, China - Xu, Xiang; Li, Shu Q. (Zootaxa, 2006)
A new species of Coelotinae from mountains of Sichuan, China, Tonsilla defossa sp. nov., is described and illustrated. The new species can be distinguished from other Tonsilla species by the thick patellar apophysis and the fishtail-shaped conductor in male, and by the strongly reduced atrium and the hidden spermathecal heads in female.